PENGARUH PENGGUNAAN BAHASA MELAYU AMBON TERHADAP PEMBENTUKAN IDENTITAS ORANG MALUKU - Marleen Muskita; Josephus Noya; Ernie Lumaupuy (JURNAL BADATI, 2023)
The use of Malay as an intermediary language throughout the Indonesian archipelago is linked to the rise of Islamic kingdoms and the spread of Islam, which was a result of the growth of regional trade. Ambonese Malay is one of the regional languages used by the Moluccan people. Ambonese Malay is spoken by most Moluccans which includes Ambon City, Lease Islands and so on. The purpose of this study is to determine and analyze the influence of the use of Ambonese Malay on the formation of Moluccan identity. From the results of the study, it was obtained that the use of Ambonese Malay had a positive and significant effect on the formation of Moluccan identity. It can be seen from the results of the partial test (t test), namely t count 11,553 t table 1,667. Then it can be concluded that the hypothesis is acceptable. The value of the coefficient of determination (R2). At 0.666 or 66.6%. This shows that the percentage of influence of Ambonese Malay on the formation of Moluccan identity is 66.6% while the remaining 33.4% is influenced by other variables that are not found in other models.